Qualidade do leite de vacas em torneios leiteiros - ROSA, Poliana P. S. G. (2015)
The objective of this research was to evaluate the physicochemical characteristics of the Dutch and crossbred cows milk originating from dairy tournaments, in the southern region of Minas Gerais, in the period from March to October 2012, using the nonparametric data for protein, fat, lactose, total solids, nonfat dry extract and somatic cell count variables. Normative Instruction 62 establishes maximum levels of somatic cell count of 500,000 cells / ml of milk, minimum fat content of 3.0%, total solids 11.4%, 2.9% protein, dry extract 8.4%. The somatic cell count reflects the health of the mammary gland of the animal. Of the 108 samples of milk collected from cows participants on the last day of the milk match, after complete milking and weighing of milk, 24% of the animals showed somatic cell counts that do not fit the parameters established by the Normative Instruction 62. The other parameters evaluated as lactose, fat, total solids and nonfat dry extract showed significant differences by comparing the milk with high somatic cell count, milk with low somatic cell count. The level of milk protein with high somatic cell count remained in the Normative Instruction 62 standard, because of the increase of plasma proteins in milk as a result of the inflammatory response. Most milk samples from dairy tournaments did not fit in Instruction 62, as the increase in somatic cells interfered in the chemical physical quality.